2021
DOI: 10.1002/ejp.1868
|View full text |Cite
|
Sign up to set email alerts
|

Patients’ self‐reported physical and psychological effects of opioid use in chronic noncancer pain—A retrospective cross‐sectional analysis

Abstract: This is an open access article under the terms of the Creat ive Commo ns Attri butio n-NonCo mmerc ial-NoDerivs License, which permits use and distribution in any medium, provided the original work is properly cited, the use is non-commercial and no modifications or adaptations are made.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Opioids may impair the assessment of one's own quality of life through central nervous system side effects depending on the dose, speed of dose escalation and on comorbidities and co-medication [44]. Patients' self-reported physical and psychological effects of opioid use in chronic non-cancer pain showed that improvement in general well-being irrespective of pain relief was experienced by 40% of the patients with chronic pain and opioid intake [45].…”
Section: Discussionmentioning
confidence: 99%
“…Opioids may impair the assessment of one's own quality of life through central nervous system side effects depending on the dose, speed of dose escalation and on comorbidities and co-medication [44]. Patients' self-reported physical and psychological effects of opioid use in chronic non-cancer pain showed that improvement in general well-being irrespective of pain relief was experienced by 40% of the patients with chronic pain and opioid intake [45].…”
Section: Discussionmentioning
confidence: 99%
“…Patients, on the other hand, initially have no experience with the intervention; they can refer only to summary descriptions of benefits and harms such as fact boxes ( Fig. 1 ); with time, however, they move from being an “experiential blank slate” to an “experiential authority” (e.g., experiencing the consequences of long-term use of strong opioids; Schulte et al, 2021 ). Furthermore, the lessons that description and experience convey do not necessarily converge; they sometimes contradict each other.…”
mentioning
confidence: 99%